Supramolecular Radical Switches Regulated by Host‐Guest Chemistry. Issue 21 (23rd August 2022) - Ye, Yu‐Yuan; Wang, Zi‐Xin; Xu, Shi‐Yuan; Lin, Xiao‐Wei; Luo, Jie; Li, Wen‐Zhen; Wang, Xiao‐Qiang
Comprehensive Summary: Water‐soluble thermal initiators are important radical sources to be applied in various fields. However, the uncontrolled radical generation from the high sensitivity of initiators may cause disadvantages in the applications. Here, we present a series of supramolecular radical switches regulated by the host‐guest chemistry between initiators and cucurbit[8]uril (CB [8]). Thermal initiators (VA‐044, VA‐056, VA‐057) can be spontaneously encapsulated into the cavity of CB [8] to "turn off" their radical‐generation ability. Their activity will instantaneously "turn on" in the presence of other competitors such as 1‐adamantylamine (ADA). Further, we demonstrated the free radical polymerization of N ‐isopropylacrylamide using initiators, inhibiting its activity by binding with CB [8] and initiating reaction by adding ADA. These novel supramolecular radical switches provide a facile strategy to control the generation of free radicals in a "plug‐and‐play" manner, which may arouse research interests in polymerization, catalysis, and the biomedical field. Abstract : A series of "plug‐and‐play" supramolecular radical switches are presented for the reversible "turn‐off" and "turn‐on" of their radical generation ability.